Political discourse through the lens of gendered language : A critical discourse analysis of four United States politicians’ speeches - Lindfors, Viveca (My University, 2024)
Since the publication of Robin Lakoff’s “Language and a woman’s place”, gendered language has become a widely researched topic in the field of linguistics. This is for good reason, as gendered language is prevalent in practically any and every setting of our daily lives and works to reinforce gender stereotypes and patriarchal social order. My research questions concerned the differences in linguistic expression between men and women as discussed by Eckert and McConnel-Ginet (2003, 2012) as well as the self-oppression of women through language described by Lazar (2005). More specifically, I investigated the degree to which the self-oppression and self-repression of women through language held true in the context of political speeches. To conduct the research for my thesis, I analysed the speeches of four American federal-level politicians. In terms of method, I focused on six linguistic features: face-building and politeness (Brown and Levinson 1987; Goffman, 1967; Holmes 1995), lexicon, syntax, speech acts (Searle 1979) and emotive language, as discussed by Eckert and McConnel-Ginet (2003, 2013) in relation to gender. In addition, I assessed deliberative rhetoric (Fairclough and Fairclough 2012) and Us vs Them positioning (van Dijk 1993, 1997). The biggest differences between the men and women were found in face-building strategies. More specifically, the women claimed face or sought approval through affiliation with men. After comparing my findings, I concluded that it is possible to consciously affect the degree of self repression and stereotyping, mainly through what Walsh (2001) refers to as the accommodation model. An even better alternative, however, would be to challenge the idea of femininity being unprofessional on a societal level.

Siitä lähtien kun Robin Lakoffin "Language and a woman's place" julkaistiin, on sukupuolittunut kieli ollut laajan mielenkiinnon kohteena lingvistiikassa. Tälle on hyvä syy, sillä sukupuolittunut kieli on läsnä käytännössä kaikilla elämän osa-alueilla ja sitä käytetään ylläpitämään sukupuolistereotypioita ja patriarkaattia. Tutkimuskysymykseni koskivat Eckertin ja McConnel-Ginetin (2003, 2012) kuvailemia kielellisen ilmaisun eroja miesten ja naisten välillä, sekä Lazarin (2005) kuvaamaa naisten itsensä tukahduttamista. Tarkemmin ottaen tutkin sitä, miten paljon naiset poliittisessa kontekstissa tukahduttivat itseään. Toteutin tutkimukseni analysoimalla neljän Yhdysvaltalaisen liittovaltiotason poliitikon puheita, keskittyen erityisesti kuuteen lingvistiseen piirteeseen: kasvot ja kohteliaisuus (Brown ja Levinson 1987; Goffman 1967; Holmes 1995), sanasto, syntaksi ja puheaktit (Searle 1979), sekä tunteellinen kieli (Eckert ja McConnel-Ginet 2003, 2013). Näiden lisäksi tutkin puheissa esiintyvää deliberatiivista retoriikkaa (Fairclough ja Fairclough 2012), sekä vastakkainasettelua (van Dijk 1993, 1997). Suurimmat erot miesten ja naisten välillä ilmenivät kasvojen rakentamisessa, tarkemmin ottaen naiset rakensivat kasvojaan ja hakivat hyväksyntää itselleen vetoamalla yhteyksiinsä korkeissa asemissa oleviin miehiin. Vertailtuani tutkimustuloksiani tulin siihen johtopäätökseen, että on mahdollista pyrkiä tietoisesti vaikuttamaan itserepressioon ja stereotypioihin Walshin (2001) kuvaileman mukautumismallin avulla. Vielä parempi vaihtoehto kuitenkin olisi haastaa yhteiskunnallinen käsitys feminiinisyydestä epäammattimaisena.
Keywords: political discourse, gendered language, discourse analysis, political discourse analysis.